A novel method of C1–C2 transarticular screw insertion for symptomatic atlantoaxial instability using a customized guiding block: A case report and a technical note. Issue 43 (October 2016) - Huang, Kuo-Yuan; Lin, Ruey-Mo; Fang, Jing-Jing
Abstract : Abstract: Atlantoaxial instability treated with the C1-2 transarticular screw fixation is biomechanically more stable; however, the technique demanding and the potential risk of neurovascular injury create difficulties for clinical usage, and there is still lack of clinical experience till now. We reported an adult female patient with symptomatic atlantoaxial instability due to rheumatoid arthritis that was successfully treated with a bilateral C1–C2 transarticular screw fixation using a customized guiding block. We preoperatively determined the trajectories for bilateral C1–C2 transarticular screws on a 3-dimensional reconstruction model from the computed tomography (CT) and self-developed computer software, and designed a rapid prototyping customized guiding block in order to offer a guide for the entry point and insertion angle of the C1–C2 transarticular screws. The clinical outcome was good, and the follow-up period was >3 years. The accuracy of the screws is good in comparison with preoperative and postoperative CT findings, and no neurovascular injury occurred. The patient was accurately and successfully treated with a bilateral C1–C2 transarticular screw fixation using a customized guiding block.